1999
DOI: 10.1007/bf02469167
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of an obliquely incident solitary wave

Abstract: on the interaction of a solitary wave of amplitude al with a plane vertical wall on which the wave is incident at angle !bl. It is established that, depending on the value of ~bi, the reflection of the wave from the wall can be regular or irregular (Mach reflection). In regular reflection, the crests of the incident and reflected waves intersect on the wall, and in Mach reflection, a third wave, called the Mach stem, appears between the wall and the point of intersection between the crests of the first two wav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…Longuet-Higgins & Fenton 1974). A similar numerical study was conducted by Barakhnin & Khakimzyanov (1999) and it was found that the values of ψ r , ψ w and α r are well predicted by Miles's theory with small amplitude, a i = 0.05, but not stem amplification, α w .…”
supporting
confidence: 60%
See 1 more Smart Citation
“…Longuet-Higgins & Fenton 1974). A similar numerical study was conducted by Barakhnin & Khakimzyanov (1999) and it was found that the values of ψ r , ψ w and α r are well predicted by Miles's theory with small amplitude, a i = 0.05, but not stem amplification, α w .…”
supporting
confidence: 60%
“…On the other hand, previous laboratory experiments failed to verify Miles's theory, and so did the higher-order numerical simulations by Tanaka (1993) and Barakhnin & Khakimzyanov (1999); the observed or simulated features and behaviours do not match the theoretical predictions.…”
Section: On Incident Wave Angle ψ Imentioning
confidence: 78%
“…These properties of the (3142)-type solution are the same as those of Miles's asymptotic solution for the Mach reflection of a shallow water soliton [22]. However one should note that the [1,4]-soliton corresponding to the Mach stem becomes a soliton solution only in an asymptotic sense. Then the exact solution of (3142)-type can provide an estimate of a propagation distance, at which the amplitude is sufficiently developed.…”
Section: The Mach Reflection and The Kp Solutionsmentioning
confidence: 53%
“…As was shown in [3], [4], each τ -function (16) generates a soliton solution which consists of at most two line-solitons for both y → ±∞. We consider the following two types which are relevant to the solutions of the initial value problems for the Mach reflection: one consists of two line-solitons of [1,2] and [3,4] for both |Y | 0, which is called O-type soliton ("O" stands for original, see [16], [4]); the other one consists of [1,3] and [3,4] line-solitons for Y 0 and [1,2] and [2,4] line-solitons for Y 0. Let us call this soliton (3142)-type, because those four line-solitons represent a permutation π = 1 2 3 4 3 1 4 2 .…”
Section: The Mach Reflection and The Kp Solutionsmentioning
confidence: 98%
See 1 more Smart Citation